Foreword: Tatars in Finland in the Transnational Context of the Baltic Sea Region - Sabira Ståhlberg; Sebastian Cwiklinksi (Studia Orientalia Electronica, 2020)
The Tatar diaspora in Finland has attracted researchers for over a century, but studies traditionally focus on topics such as origins and general Tatar history, religion, identity or language. One of the most important aspects of research on Tatars both historically and today, however, is the transnational context. Migrating from villages in Nizhny Novgorod province, often via the Russian capital Saint Petersburg at the end of the nineteenth century, the forming Tatar diaspora communities in the Baltic Sea region maintained, developed and extended their previous networks and also created new connections over national borders despite periods of political difficulties. New research about Tatars in the Baltic Sea region – with the focal point of the Tatars in Finland and their connections chiefly in Estonia, Russia and Sweden – was presented during a seminar called Tatars in Finland in the Transnational Context of the Baltic Sea Region at the University of Helsinki in October 2018. Scholars from Finland, Sweden, Russia, Estonia and Hungary spoke about the past and present of the diaspora. A result of the seminar, this special issue of Studia Orientalia Electronica is dedicated to new research on Tatars in a transnational context.